Labor Migration Trends in Vietnam in The Period 2014-2018 - Thi Minh Hang Bui; Thi Thanh Huyen Nguyen; Thi Lan Anh Nguyen (RIRAI Publisher, 2023)
Information about labor migration plays an important role in planning and implementing socio-economic development policies in each region and for the whole country. This study used data from Vietnam Household Living Standards Survey 2018, 2016 and 2014 conducted by the General Statistics Office of Vietnam to analyze labor migration trends based on demographic characteristics and regional features. Statistical results show that the percentage of labor migrants tended to increase in the period 2014-2018. The results show that demographic factors such as ethnicity, age, gender, marital status, and education had a strong relationship with labor migration flows. In addition, there was a positive correlation between regional characteristics such as unemployment and underemployment and labor migration. By understanding the demographic and regional characteristics that influence specific groups of migrant workers, policymakers can establish target policies to effectively control labor migration flows